150k views
4 votes
Use the method of completing the square to solve y²+y-7=0​

2 Answers

2 votes

Answer:

y=sqrt(29)/2-1/2, -sqrt(29)/2-1/2

Explanation:

y^2+y-7=0

completing the square,

(b/2)^2=(1/2)^2=1/4

(y+1/2)^2=7+1/4

(y+1/2)^2=28/4+1/4

(y+1/2)^2=29/4

y+1/2=sqrt(29/4)

y=sqrt(29/4)-1/2

y=sqrt(29)/2-1/2

y=-sqrt(29)/2-1/2

User Iren Patel
by
5.9k points
6 votes

Answer:

y = sqrt(29)/2 - 1/2 or y = -1/2 - sqrt(29)/2

Explanation:

Solve for y:

y^2 + y - 7 = 0

Add 7 to both sides:

y^2 + y = 7

Add 1/4 to both sides:

y^2 + y + 1/4 = 29/4

Write the left hand side as a square:

(y + 1/2)^2 = 29/4

Take the square root of both sides:

y + 1/2 = sqrt(29)/2 or y + 1/2 = -sqrt(29)/2

Subtract 1/2 from both sides:

y = sqrt(29)/2 - 1/2 or y + 1/2 = -sqrt(29)/2

Subtract 1/2 from both sides:

Answer: y = sqrt(29)/2 - 1/2 or y = -1/2 - sqrt(29)/2

User Vincent Sels
by
5.4k points